Insulin Resistance and Pellino-1 Mediated Decrease in the Activities of Vasodilator Signaling Contributes to Sunitinib-Induced Hypertension - Liu, Yang; Tang, Liang-Liang; Liang, Chen; Wu, Ming-Ming; Zhang, Zhi-Ren (Frontiers in Pharmacology, 2021)
Antiangiogenic tyrosine kinases inhibitors (TKIs) induce hypertension, which may increase the incidents of cardiovascular complications and limit their use. However, the mechanisms by which usage of TKIs results in hypertension have not been fully understood. Here, we report the potential mechanisms of how sunitinib, a widely used TKI, induces hypertension. Male SD rats were randomly divided into control group and sunitinib-administrated group. We show that sunitinib administration for seven days caused a significant increase in artery BP, along with glycerolipid metabolism abnormalities including decreased food intake and low body weight, hypoglycemia, hyperinsulinemia. Sunitinib administration also resulted in a significant increase in the levels of insulin autoantibody (IAA), cyclic adenosine monophosphate (cAMP) and free fatty acid (FFA) in serum; whereas, sunitinib administration had no effects on serum glucagon (GC) levels. Sunitinib led to the decreased insulin sensitivity as determined by insulin tolerance test (ITT) and glucose tolerance test (GTT), reflecting insulin resistance occurred in sunitinib-treated rats. The results obtained from wire myograph assay in the mesenteric arteries show that endothelium-dependent relaxation, but not endothelium-independent relaxation, was impaired by sunitinib. Furthermore, western blot analysis revealed that the expressions levels of phosphorylated IRS-1, Pellino-1, AKT and eNOS were significantly attenuated by sunitinib in rat mesenteric artery tissues and in the sunitinib-treated primary cultured mesenteric artery endothelial cells (MAECs). The levels of serum and endothelium-derived NO were also significantly decreased by sunitinib. Moreover, sunitinib-induced decrease in the expression levels of phosphorylated AKT and eNOS was further reduced by knocking down of Pellino-1 in MAECs. Our results suggest that sunitinib causes vascular dysfunction and hypertension, which are associated with insulin resistance- and Pellino-1-mediated inhibition of AKT/eNOS/NO signaling. Our results may provide a rational for preventing and/or treating sunitinib-induced endothelial dysfunction and hypertension.